Targeting CD47 as a Novel Immunotherapy for Breast Cancer - Chen, Can; Wang, Runlu; Chen, Xi; Hou, Yulong; Jiang, Jingting (Frontiers in Oncology, 2022)
Nowadays, breast cancer has become the most commonly diagnosed cancer worldwide with high mortality rate. Immune checkpoint blockade holds great promise in tumor‐targeted therapy, and CD47 blockade as one immune checkpoint therapy is undergoing various preclinical studies and clinical trials to demonstrate its safety and efficacy in breast cancer. In this review, we summarize different therapeutic mechanisms to target CD47 and its prognostic role and therapeutic value in breast cancer.